On the future navigability of Arctic sea routes: High-resolution projections of the Arctic Ocean and sea ice. (January 2017) - Aksenov, Yevgeny; Popova, Ekaterina E.; Yool, Andrew; Nurser, A.J. George; Williams, Timothy D.; Bertino, Laurent; Bergh, Jon
Abstract: The rapid Arctic summer sea ice reduction in the last decade has lead to debates in the maritime industries on the possibility of an increase in cargo transportation in the region. Average sailing times on the North Sea Route along the Siberian Coast have fallen from 20 days in the 1990s to 11 days in 2012–2013, attributed to easing sea ice conditions along the Siberian coast. However, the economic risk of exploiting the Arctic shipping routes is substantial. Here a detailed high-resolution projection of ocean and sea ice to the end of the 21st century forced with the RCP8.5 IPCC emission scenario is used to examine navigability of the Arctic sea routes. In summer, opening of large areas of the Arctic Ocean previously covered by pack ice to the wind and surface waves leads to Arctic pack ice cover evolving into the Marginal Ice Zone. The emerging state of the Arctic Ocean features more fragmented thinner sea ice, stronger winds, ocean currents and waves. By the mid 21st century, summer season sailing times along the route via the North Pole are estimated to be 13–17 days, which could make this route as fast as the North Sea Route. Highlights: A high-resolution projection for the Arctic Ocean in the 21st century is examined. Future navigability of the Arctic sea routes and sailing times are assessed. Increased wind and waves transform pack ice into fragmented Marginal Ice Zone. Arctic transit shipping saves time and fuel but may add to Arctic warming. Forecasting requirements for the new emerging state of the Arctic are discussed.